2023
DOI: 10.1007/s12072-022-10478-6
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant anti-PD-1 antibody for hepatocellular carcinoma with high recurrence risks after hepatectomy

Abstract: Background and PurposeThe clinical role of postoperative adjuvant therapy in hepatocellular carcinoma (HCC) is still unclear. The purpose of our study was to explore the clinical value of postoperative adjuvant anti-programed cell death 1 antibody (PA-PD-1) on the prognosis of HCC patients with high relapse risks after surgery. Patients and MethodsConsecutive HCC patients with high recurrence risks treated with liver resection at our center during January 2019 and March 2021 were prospectively enrolled. Baseli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
2
15
2
Order By: Relevance
“…Therefore, the larger the tumor, the higher the probability of microsatellite foci around the tumor, the emergence of MVI, and the increased the likelihood of tumor recurrence. Although a radical treatment, TACE in combination with MWA fails to eradicate microsatellite foci that cannot be detected by imaging around the tumor tissue, and the combination of lenvatinib and PD-1 antibodies can eliminate microsatellite foci, thus enhancing the anti-tumor effect (12,18). Multivariable analysis showed that the tumor number was a risk factor for PFS2, regardless of whether adjuvant therapy was administered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the larger the tumor, the higher the probability of microsatellite foci around the tumor, the emergence of MVI, and the increased the likelihood of tumor recurrence. Although a radical treatment, TACE in combination with MWA fails to eradicate microsatellite foci that cannot be detected by imaging around the tumor tissue, and the combination of lenvatinib and PD-1 antibodies can eliminate microsatellite foci, thus enhancing the anti-tumor effect (12,18). Multivariable analysis showed that the tumor number was a risk factor for PFS2, regardless of whether adjuvant therapy was administered.…”
Section: Discussionmentioning
confidence: 99%
“…Lenvatinib and immune checkpoint inhibitors (ICIs) have been approved for use in patients with advanced unresectable HCC and are now widely used in clinical practice (8)(9)(10). Recent studies indicate that adjuvant lenvatinib following hepatectomy improves the early RFS rate of HCC patients with MVI by approximately 17.1%-27.3% (11), while adjuvant PD-1 antibodies improves the early RFS by approximately 22.8%-24.4% in HCC patients who have a combination of high-risk factors for recurrence after hepatectomy, such as portal vein tumor thrombus or tumor size of ≥5 cm (12). However, there is no consensus on the use of tyrosine kinase inhibitors (TKIs) and PD-1 antibodies as adjuvant therapies after resection or ablation of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Masatoshi Kudo et al ( 83) evaluated the efficacy and safety of adjuvant nivolumab after LR or ablation for HCC in a single-arm study, the median DFS was 26.3 months and the AEs was manageable. And Chen et al (84) revealed the value of PD-1 inhibitors as adjuvant therapy in a recent cohort study, where patients had significantly better DFS than controls (After PSM, the 2-year DFS was 44.1% vs 21.3%). Similarly, some studies found that adjuvant PD-1 inhibitors also helpful in prolonging DFS for other cancers following surgery such as melanoma, esophageal, and gastroesophageal tumors (85,86).…”
Section: Immunotherapies Including Lymphocyte Infusions Cytokineinduc...mentioning
confidence: 99%
“…And Chen et al. ( 84 ) revealed the value of PD-1 inhibitors as adjuvant therapy in a recent cohort study, where patients had significantly better DFS than controls (After PSM, the 2-year DFS was 44.1% vs 21.3%). Similarly, some studies found that adjuvant PD-1 inhibitors also helpful in prolonging DFS for other cancers following surgery such as melanoma, esophageal, and gastroesophageal tumors ( 85 , 86 ).…”
Section: The Current Options and Recent Advances Of Adjuvant Therapymentioning
confidence: 99%
“…Some preliminary results indicate that postoperative PD-1 antibodies can effectively extend the survival of high-risk patients. Researchers like Chen et al ( 14 ). believe that HCC patients with portal vein tumor thrombosis (PVTT) or tumors larger than or equal to 5 cm significantly benefit from anti-PD-1 antibody treatment in terms of and OS.…”
Section: Introductionmentioning
confidence: 99%